2015
DOI: 10.17762/ijnpme.v4i01.34
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Speech Recognition in Mobile Customer Care Service

Abstract: In the project an automatic speech system is used in mobile customer care   services. In existing  mobile  customer care  services, customer  have  to  wait for 4 to 5 minutes  to get  into the  option  what   they  want to  inquire. Based on the requirement, we go for filtering the incoming calls. Persons who require particular data are dynamically move to speech recognition system that identifies the type of the enquiry chosen. Speech recognition is the one which dynamically identifies the individual speakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…For this test [24,25], only continuous, unidirectional fibers that are the same length as the specimen may be used. By applying an indentation load that is both normal to the fibre length and normal to the fibre diameter [26,27], the hardness characteristics of the composites are examined. It is observed that the ultimate tensile strength (UTS) of 19.3 MPa was found in sample number 6, attributed to the strong bonding between fibers KA and KC.…”
Section: Hardness Testmentioning
confidence: 99%
“…For this test [24,25], only continuous, unidirectional fibers that are the same length as the specimen may be used. By applying an indentation load that is both normal to the fibre length and normal to the fibre diameter [26,27], the hardness characteristics of the composites are examined. It is observed that the ultimate tensile strength (UTS) of 19.3 MPa was found in sample number 6, attributed to the strong bonding between fibers KA and KC.…”
Section: Hardness Testmentioning
confidence: 99%
“…The chapter discusses various theoretical frameworks and instructional approaches to address and mitigate language anxiety in educational contexts. In [35] explores the concept of emotion regulation in the context of language teaching. The authors discuss strategies that language teachers can employ to regulate their own emotions and create an emotionally supportive learning environment.…”
Section: International Journal On Recent and Innovation Trends In Com...mentioning
confidence: 99%
“…Despite the fact that the semantic information in these user profile models allows them to properly reflect the content of the user's interested Web pages, it remains a challenge to evolve and maintain the model's adaptiveness in order to signify the consumer's interests by limited subjects. Singh et al propose a news filtering system that models the user's preferences using an interest hierarchy based on explicit user feedback [7]. Due to the lack of semantics, dynamics, and adaptability in current research, it is difficult to adequately capture users' real-time interests that affect the quality of tailored suggestions.…”
Section: Related Workmentioning
confidence: 99%